2021
DOI: 10.5194/acp-2021-735
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measurement report: Long-term measurements of aerosol precursor concentrations in the Finnish sub-Arctic boreal forest

Abstract: Abstract. Aerosol particles form in the atmosphere by clustering of certain atmospheric vapors. After growing to larger particles by condensation of low volatile gases, they can affect the Earth’s climate directly by scattering light and indirectly by acting as cloud condensation nuclei. Observations of low-volatility aerosol precursor gases have been reported around the world but longer-term measurement series and any Arctic data sets showing seasonal variation are close to non-existent. In here, we present ~… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…The daytime increase can be explained by sunny conditions warming the air during the day. This trend is similar to whatJokinen et al (2021) observed in Northern Finland.…”
supporting
confidence: 91%
“…The daytime increase can be explained by sunny conditions warming the air during the day. This trend is similar to whatJokinen et al (2021) observed in Northern Finland.…”
supporting
confidence: 91%
“…All meteorological parameters, trace gas concentrations and aerosol data were downloaded directly from the SmartSMEAR open-access database: https://smear.avaa.csc.fi/ (Junninen et al, 2009). Mass spectrometric data, event analysis, and condensation sink and anion concentration data are available from Zenodo: https://doi.org/10.5281/zenodo.5879549 (Jokinen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%